Regarding One Cointegration Task of Trade Relations Between Ukraine, Azerbaijan and Georgia - Alizade Arzu Rafik (Bìznes Inform, 2022)
In this article, the integration processes between Azerbaijan, Ukraine and Georgia are considered through the indicators of integratedness of Azerbaijan’s GDP and the trade turnover of this country with the other two. All the time series considered are non-stationary. Therefore, the construction of a model of correlation-regression analysis will lead to the obtainment of shifted estimates of the coefficients. So, there are problems of correct modeling of the corresponding time series, the components of which lead to a deviation from stationarity. The publication uses an econometric integration methodology for modeling the relationship between the non-stationary time series. The modeling correctly used econometric methods, all the necessary step-by-step statistical procedures to determine the order of integration of the non-stationary time series – to identify and evaluate the parameters of the model and to check its adequacy and accuracy of both the short-term and the long-term forecast values using the tools of Excel and the EViews 8 package. An analysis of empirical tests for their deviation from the trend was carried out. The speeds of elimination of the imbalance and the visible convergences of the corrective system from the equilibrium trajectory are determined. A dynamic model of the long-term equilibrium is built, allowing to qualitatively forecast the state of foreign trade integration of the three countries under consideration and analyze the openness of the Azerbaijani economy in the regional aspect. As a result of the constructed model, econometric substantiated recommendations have been developed that allow for a dynamic analysis of effective State regulation of export-import operations between these countries to balance mutual trade.